Peran Religiusitas dan Modal Sosial Terhadap Kinerja Karyawan - Menrizal .; Ririn Handayani; Fahmi Oema (CV. ITTC INDONESIA, 2026)
The study was conducted at the Al-Ubudiyah Hajj and Umrah Guidance Group (KBIHU), Al Ubudiyah Waqf Foundation Pekanbaru, with the aim of examining the role of social capital in mediating the influence of religiosity on performance. The population of this study was 100 people. Based on this population size, the entire population was sampled so that the sample size for this study was 100 people. The sampling method used in this study was the saturated sampling method. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that religiosity has a significant positive effect on performance, religiosity has a significant positive effect on social capital, social capital has a significant positive effect on performance, and social capital mediates the effect of religiosity on social capital.